Crossing the North Sea for Books. An Overview of the Scottish Book Trade with the Officina Plantiniana between 1555 and 1589. (18th June 2019) - Van Loon, Zanna
Abstract: The Officina Plantiniana is known to have had an international scope in the sixteenth century, selling books to different European regions, including Scotland. This article uses the records of the Plantin–Moretus archives to show that forty Scotsmen approached the Officina between 1555 and 1589. It focuses on both booksellers and merchants, as well as private clients. While it identifies them and their and place in Scottish society, it also concentrates on when they traded with the printing office of Plantin, in light of the early-modern political and religious context. Additionally, this paper briefly explores to what extent Plantin met with the Scottish demand for scholarly books. This case study therefore not only examines the role Plantin had in the Latin Trade with Scotland, but also considers the way this trade came under the influence of sixteenth-century confessionalization.